2023
DOI: 10.1098/rsos.221473
|View full text |Cite
|
Sign up to set email alerts
|

Walking like a robot: do the ground reaction forces still intersect near one point when humans imitate a humanoid robot?

Abstract: Bipedal walking while keeping the upper body upright is a complex task. One strategy to cope with this task is to direct the ground reaction forces toward a point above the centre of mass of the whole body, called virtual pivot point (VPP). This behaviour could be observed in various experimental studies for human and animal walking, but not for the humanoid robot LOLA. The question arose whether humans still show a VPP when walking like LOLA. For this purpose, ten participants imitated LOLA in speed, posture,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
(77 reference statements)
2
2
0
Order By: Relevance
“…However, although the values are not statistically significant, a larger scatter and tendency for lower R 2 values for these conditions can be observed ( The VPP variables (position and R 2 ) confirm former studies, especially for the baseline conditions barefoot and shoe walking [1,2,8,9,21]. Until now, all human gait experiments regarding the perturbation of the VPP could show the point, except for single outliers [4,8,9,21]. Thus it may be concluded that the VPP has a fundamental function for upright human gait.…”
Section: Plos Onesupporting
confidence: 79%
See 2 more Smart Citations
“…However, although the values are not statistically significant, a larger scatter and tendency for lower R 2 values for these conditions can be observed ( The VPP variables (position and R 2 ) confirm former studies, especially for the baseline conditions barefoot and shoe walking [1,2,8,9,21]. Until now, all human gait experiments regarding the perturbation of the VPP could show the point, except for single outliers [4,8,9,21]. Thus it may be concluded that the VPP has a fundamental function for upright human gait.…”
Section: Plos Onesupporting
confidence: 79%
“…Only for single outliers (e.g. this study and [21]) the VPP input variables seem not to be able to compensate each other. Following from that it would be interesting to find perturbations of the entire interaction of the musculoskeletal system.…”
Section: Future Considerationsmentioning
confidence: 75%
See 1 more Smart Citation
“…Therefore, when calculating the GRFs for walking, different positions of the VPP during double and single support should be considered in a future study. Furthermore, while walking with bent legs which can be compared with the lunge posture of the present study, Vielemeyer et al (2023b) observed a (cranial) shift in the VPP position.…”
Section: Discussionsupporting
confidence: 59%